2010
DOI: 10.2478/v10051-010-0019-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management in the Hotel Industry Before and After the Entry in the EU: The Case of Slovenia

Abstract: Knowledge Management in the Hotel Industry Before and After the Entry in the EU: The Case of SloveniaThe paper deals with the impact of the EU entry on knowledge management in the hotel industry in Slovenia. For this purpose, the empirical research on knowledge management was carried out among hotel managers. It explored the changes in knowledge management between 2003 and 2006; that is before and after Slovenia entered the EU. The research revealed a progress in this period of time in knowledge management goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Liyanage et al (2009) indicated that KA is the critical part of the KM process. It is at this stage that the value of knowledge is manifested (Rudež, 2010). As this study shows, front-line employees’ SRP is significantly and greatly influenced by KA.…”
Section: Discussion Conclusion and Recommendationmentioning
confidence: 99%
See 2 more Smart Citations
“…Liyanage et al (2009) indicated that KA is the critical part of the KM process. It is at this stage that the value of knowledge is manifested (Rudež, 2010). As this study shows, front-line employees’ SRP is significantly and greatly influenced by KA.…”
Section: Discussion Conclusion and Recommendationmentioning
confidence: 99%
“…Effective and successful KM in the hotel sector is essential to the success of hotels (Rudež, 2010). However, the hotel sector is far behind when it comes to existing KM practices (Hallin and Marnburg, 2008).…”
Section: The Hospitality Industry In Ghanamentioning
confidence: 99%
See 1 more Smart Citation
“…Various definitions of KM have been presented by scholars, emphasizing the importance of continued KM research (Groff and Jones, 2003; Mahaba, 2013; Neves et al., 2014; Rudez, 2010; Skyrme, 2002; Villar et al., 2014). However, there is neither clear consensus on the definition of KM as a process nor there is an established theme for KM research to classify or group the directions and findings of related research attempts.…”
Section: Key Concepts and Theoretical Assumptionsmentioning
confidence: 99%
“…As for KM application in the hotel industry, various research attempts are available. Rudez (2010) studied KM in the Slovenian hotel industry before and after the entry in the EU, studying the impact of the EU entry on KM in the hotel industry in Slovenia between 2003 and 2006. The research revealed a progress in this period of time in KM goals definition, transformation of not-owned into owned knowledge, inclusion of KM in business reports, identification, and elimination of the gaps between planned and actual knowledge.…”
Section: Introductionmentioning
confidence: 99%